The impact of natural disasters, technological change and education on poverty rate: evidence from developing countries - Jaharudin Padli,; Nizam Ahmat,; Mohd Nasir Nawawi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to analyze the impacts of natural disasters (total affected and total damages), technological change and education on poverty rates using 38 selected developing countries over the period of 1984-2013. A panel regression method is used in estimating the model. The results show that more impactful natural calamities will increase the poverty rate (positive relationships), while the impact of technological change has brought the poverty rate down to the lowest level (negative relationships). However, this study finds positive relationships between technological change and poverty, with an increase in technology causing a rise in poverty. The study also reveals a negative relationship between education on poverty. This implies that improvements in education can play an important role in increasing welfare and reducing poverty in developing countries. The results of this study suggest that education might be the best solution for minimizing the impact of natural disaster and poverty avoidance.